Protocol for a Process Evaluation of the Quality Improvement Intervention to Enhance Access to Kidney Transplantation and Living Kidney Donation (EnAKT LKD) Cluster-Randomized Clinical Trial. (March 2022) - Yohanna, Seychelle; Wilson, Mackenzie; Naylor, Kyla L.; Garg, Amit X.; Sontrop, Jessica M.; Belenko, Dmitri; Elliott, Lori; McKenzie, Susan; Macanovic, Sara; Mucsi, Istvan; Patzer, Rachel; Voronin, Irina; et al.
Background: Many patients who would benefit from a kidney transplant never receive one. The Enhance Access to Kidney Transplantation and Living Kidney Donation (EnAKT LKD) pragmatic, cluster-randomized clinical trial is testing whether a multi-component quality improvement intervention, provided in chronic kidney disease (CKD) programs (vs. usual care), can help patients with CKD with no recorded contraindications to kidney transplant complete more steps toward receiving a transplant (primary outcome of the trial). The EnAKT LKD intervention has 4 components: (1) quality Improvement teams and administrative support, (2) improved transplant education for patients and healthcare providers, (3) access to support and (4) program-level performance monitoring. Objective: To conduct a process evaluation of the EnAKT LKD quality improvement intervention to determine if the components were delivered, received, and enacted as designed (fidelity), and if the intervention addressed intended barriers (mechanisms of change). Design: A mixed-methods process evaluation informed by new practice implementation and theories of behavior change. Setting: Chronic kidney disease programs in Ontario, Canada, began receiving the EnAKT LKD intervention on November 1, 2017 and will continue to receive it until December 31, 2021. The process evaluation (interviews and surveys) will occur alongside the trial, between December 2020 to May 2021. Participants: Healthcare providers (eg, dialysis nurses, nephrologists, members of the multi-care kidney clinic team) at Ontario's 27 CKD programs. Methods: We will survey and interview healthcare providers at each CKD program, and complete an intervention implementation checklist. Quantitative data from the surveys and the intervention implementation checklist will assess fidelity to the intervention, while quantitative and qualitative data from surveys and interviews will provide insight into the mechanisms of change. Limitations: The long trial period may result in poor participant recall. Conclusion: This process evaluation will enhance interpretation of the trial findings, guide improvements in the intervention components, and inform future implementation. Trial registration: Clinicaltrials.gov; identifier: NCT03329521.